Comparative Analysis of Salivary Gland Proteomes of Two Glossina Species that Exhibit Differential Hytrosavirus Pathologies - Kariithi, Henry M. (Front Microbiol, 2016)
Glossina pallidipes salivary gland hypertrophy virus (GpSGHV; family Hytrosaviridae) is a dsDNA virus exclusively pathogenic to tsetse flies (Diptera; Glossinidae). The 190 kb GpSGHV genome contains 160 open reading frames and encodes more than 60 confirmed proteins. The asymptomatic GpSGHV infection in flies can convert to symptomatic infection that is characterized by overt salivary gland hypertrophy (SGH). Flies with SGH show reduced general fitness and reproductive dysfunction. Although the occurrence of SGH is an exception rather than the rule, G. pallidipes is thought to be the most susceptible to expression of overt SGH symptoms compared to other Glossina species that are largely asymptomatic. Although Glossina salivary glands (SGs) play an essential role in GpSGHV transmission, the functions of the salivary components during the virus infection are poorly understood. In this study, we used mass spectrometry to study SG proteomes of G. pallidipes and G. m. morsitans, two Glossina model species that exhibit differential GpSGHV pathologies (high and low incidence of SGH, respectively). A total of 540 host proteins were identified, of which 23 and 9 proteins were significantly up- and down-regulated, respectively, in G. pallidipes compared to G. m. morsitans. Whereas 58 GpSGHV proteins were detected in G. pallidipes F(1) progenies, only 5 viral proteins were detected in G. m. morsitans. Unlike in G. pallidipes, qPCR assay did not show any significant increase in virus titers in G. m. morsitans F(1) progenies, confirming that G. m. morsitans is less susceptible to GpSGHV infection and replication compared to G. pallidipes. Based on our results, we speculate that in the case of G. pallidipes, GpSGHV employs a repertoire of host intracellular signaling pathways for successful infection. In the case of G. m. morsitans, antiviral responses appeared to be dominant. These results are useful for designing additional tools to investigate the Glossina-GpSGHV interactions.